PREDIKSI KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR PERUSAHAAN DI BURSA EFEK INDONESIA - Surya Gandi; Damayanti Damayanti; Supriyanto Supriyanto (Jurnal Perspektif Bisnis, 2020)
Being aware the signal of financial distress conditions is important because in the worst case scenario the company can be forced in to liquidation. This condition can be predicted using model that have been developed by many researchers. The purpose of this research is analyze and describe the effects of current asset to current liability, debt to total asset, total asset turnover, and net income to equity in predicting the condition of financial distress in manufacturing companies listed in Indonesian Stock Exchange in year 2012-2017. The data analiysis method is logit regression. The resecarch sample used purposive sampling tecnique. The result of wald test (partial) showed that current asset to current liability, debt to total asset and total asset turnover that have significant effects to predict the condition of financial distress in company, whilst net income to equity not significant to predict the condition of financial distress in the company. The result of G2/likehood showed that current asset liability, debt to total asset, total asset turnover and net income to equity simultaneously have significant influence to predict the condition of financial distress in company. Value of Mc fadden R-squared (R2) showed the relation among the variabels is in a very strong category.